Optimizing bone mass and strength: The role of physical activity and nutrition during growth (Medicine and Sport Science, 51, 2007)
Osteoporosis and related fractures are a major public health problem globally. Although traditionally considered to be a disease affecting the elderly, increased recognition that osteoporosis may have its foundation early in life has stimulated substantial research interest into factors which can influence skeletal development, including both genetic and lifestyle factors. This book provides a summary and integrative review of the current state of knowledge of factors that influence the development of bone health during childhood and adolescence. The focus is on the role of physical activity for optimizing bone development. Other relevant topics that are reviewed include the influence of genetics, nutrition, and hormonal factors on skeletal development. In addition, there are expert views on practical lifestyle strategies and guidelines that can be adopted to optimize bone health and prevent fractures during growth. The book provides an excellent source of recent information for exercise specialists, pediatricians, nutritionists, biomedical researchers, health promotion worker and public health professionals. Contents: Preface Contributors Faulkner, R.A. ; Bailey, D.A.: Osteoporosis: A Pediatric Concern? Kontulainen, S.A.; Hughes, J.M.; Macdonald, H.M.; Johnston, J.D.: The Biomechanical Basis of Bone Strength Development during Growth Daly, R.M.: The Effect of Exercise on Bone Mass and Structural Geometry during Growth Specker, B.; Vukovich, M.: Evidence for an Interaction between Exercise and Nutrition for Improved Bone Health during Growth Bonjour, J.-P.; Chevalley, T.; Rizzoli, R.; Ferrari, S.: Gene-Environment Interactions in the Skeletal Response to Nutrition and Exercise during Growth Zanker, C.; Hind, K.: The Eff ect of Energy Balance on Endocrine Function and Bone Health in Youth Goulding, A.: Risk Factors for Fractures in Normally Active Children and Adolescents Karlsson, M.K.: Does Exercise during Growth Prevent Fractures in Later Life? Hughes, J.M.; Novotny, S.A.; Wetzsteon, R.J.; Petit, M.A.: Lessons Learned from School-Based Skeletal Loading Intervention Trials: Putting Research into Practice Subject Index